Factors Related To The Performance Of Pharmaceutical Employees At The Southeast Sulawesi Provincial Health Office Year 2025 - La Ode Liaumin Azim; Agnes Mersatika Hartoyo (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Employee performance in the field of health and pharmaceutical services plays a crucial role in determining the quality of services provided to the community. In the Southeast Sulawesi Provincial Health Office, various internal and external factors are believed to influence employee performance, but there has not been much research that comprehensively examines these factors. This study aims to identify and analyze factors related to employee performance in the health and pharmaceutical services sector at the Southeast Sulawesi Provincial Health Office. This study uses a quantitative design with a cross-sectional approach. This study was conducted from July 23 to August 14, 2025, at the Southeast Sulawesi Provincial Health Office. The sample consisted of 34 respondents selected through total sampling. Data analysis was performed using the chi-square test. The results of the study show that there is a relationship between educational characteristics (p value = 0.007), length of service (p value = 0.007), and motivation (p value = 0.000) with the performance of employees in the health and pharmaceutical services sector of the Southeast Sulawesi Provincial Health Office in 2024. There was no relationship between age (p value = 0.427) and gender (p value = 0.363) characteristics and the performance of employees in the health and pharmaceutical services sector of the Southeast Sulawesi Provincial Health Office. Factors such as motivation, training, and work environment play an important role in determining the performance of employees in the health and pharmaceutical services sector at the Southeast Sulawesi Provincial Health Office. Therefore, improving training programs and efforts to increase employee motivation are recommended to improve overall performance.